Functional results of compound extra articular tibial pilon fractures managed with hybrid external fixator - Raina, Gagandeep Singh; Gupta, Sanjeev; Azharuddin, Mohammad; Lone, Zubair A.; Kumar, Manoj (International Journal of Research in Orthopaedics, 2021)
Background: Distal tibia fractures are difficult to treat. It is often difficult to assess the potential risk of surgical complications because of the variations in the clinical findings. Less subcutaneous tissue, limited blood supply and no muscle insertions are the factors that tend to make the healing of the soft tissue more complex. Compounding presents a great challenge for the treating surgeon regarding the treatment options. Methods: A total of 23 patients were included in the study based on the inclusion and exclusion criteria and were managed by hybrid external fixator as definitive treatment. They were kept in follow up for at least 6 months and were assessed using Ovadia and Beal’s objective and subjective scoring. Results: All patients achieved fracture union with 82% patients reporting excellent to good functional outcome. Pin site infections and ankle stiffness were most common complications. Conclusions: A very good outcome is achieved in compound extra articular tibial pilon fractures with the hybrid fixator technique. Adequate stability is provided and hence early motion and ambulation can be started.